CELIAC AND AUTOIMMUNE THYROID DISEASE IN PATIENTS WITH ANTI-GAD POSITIVE TYPE-1 DIABETES MELLITUS - Versha Rani Rai; Zubair Khoso; Maira Riaz; Roshia Parveen; Shazia Mahar; Mohsina Noor (Journal of Ayub Medical College Abbottabad, 2023)
Background: Type-1 diabetes mellitus (T1DM) and autoimmune thyroid disease can occur concomitantly and patients with TIDM have a high risk of other autoimmune conditions like thyroid disease and celiac disease. This study aimed to analyze the association of anti-GAD positive T1DM with anti-thyroid antibodies and celiac disease. Methods: This cross-sectional study was conducted at the Department of Paediatric Endocrinology & Diabetes, National Institute of Child Health, Karachi Pakistan from July 2022 to December 2022. A total of 115 children of both genders aged between 1-18 years having known T1DM were analyzed. Children with chronic kidney disease or chronic liver disease were excluded. Those children were also not included whose parents/caregivers did not wish their children to be part of this research. The blood sample of each child was taken in a sterilized container and sent to an institutional laboratory for biochemical investigations. Results: In a total of 115 patients, 67 (58.3%) were female and 48 (41.7%) males. The mean age was 8.87±3.43 (ranging between 1.5-17 years). The mean HbA1c was 11.86±7.31%. It was found that anti-GAD IgG was having signification association with celiac disease (p<0.001). Significant correlation of anti-GAD positive antibodies with Ttg-IgG antibodies (correlation coefficient=0.303, p=0.001), thyroid peroxidase antibodies (correlation coefficient=0.228, p=0.001). Conclusion: High proportions of children with anti-GAD positive T1DM patients were found to have thyroid disorders and celiac disease. A significant correlation was found between anti-GAD positive antibodies, celiac disease and anti-thyroglobulin antibodies.